2017
DOI: 10.1021/acssuschemeng.7b00132
|View full text |Cite
|
Sign up to set email alerts
|

l-Proline Functionalized Dicationic Framework of Bifunctional Mesoporous Organosilica for the Simultaneous Removal of Lead and Nitrate Ions

Abstract: A novel bifunctional mesoporous organosilica, PEG-functionalized bis-prolinium chloride bridged mesoporous organosilica (BPBMO) was synthesized by reacting the precursor, PEG-functionalized bis-prolinium chloride bridged organosilane (BPRIL) with tetraethyl orthosilicate (TEOS) in the presence of surfactant. The chemical conformation of BPBMO was investigated by using Fourier transform infrared (FTIR), thermogravimentric analysis (TGA), 13C, and 29Si cross-polarization/magic angle spinning (CP/MAS) NMR techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…From Figure 7 we can see that after adsorption, CM kept its original shape, Cu and Pb peaks became visible in the EDS spectra of CM. The binding energy of Cu is around 950 eV and that of Pb is around 140 eV, which is consistent with the binding energy of the oxidation of Cu and Pb as literatures reported 47‐48 . Figure 8 manifests that the intensity of some adsorption bands showed an obvious decrease in the FT‐IR spectra, indicating the occupation of functional groups (‐SiOH, ‐AlOH) during the adsorption which is corresponding to the results of EDS.…”
Section: Resultssupporting
confidence: 85%
“…From Figure 7 we can see that after adsorption, CM kept its original shape, Cu and Pb peaks became visible in the EDS spectra of CM. The binding energy of Cu is around 950 eV and that of Pb is around 140 eV, which is consistent with the binding energy of the oxidation of Cu and Pb as literatures reported 47‐48 . Figure 8 manifests that the intensity of some adsorption bands showed an obvious decrease in the FT‐IR spectra, indicating the occupation of functional groups (‐SiOH, ‐AlOH) during the adsorption which is corresponding to the results of EDS.…”
Section: Resultssupporting
confidence: 85%
“…It can be found that the peak of C−C/CC (at 284.69 eV) for MoS 2 @biochar after Pb 2+ adsorption shifted by 0.1 eV, indicating the chelation of Pb 2+ ions with aromatic structure (Pb-π interaction). 54 The Pb 2+ can increase the electron density by offering electrons to the aromatic structure with decreasing the binding energy of carbon atoms. As for the high-resolution O 1s spectrum of MoS 2 @biochar-Pb (Figure 7C), the new peak (at 531.11 eV) can be ascribed to the Pb−O bond.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%
“…23,34−36 Silica-based materials have intensively been studied as adsorbents in solid−liquid separation processes. 6,37 Surfacefunctionalized materials containing cationic groups have thoroughly been used for anion sorption such as arsenate, chromate, 38−41 perruthenate, 42 perrhenate, 43 or diverse radioelements. 44,45 Ammonium-and imidazolium-functionalized silica materials display improved sorption capacities due to the high quantity of functional groups located on the surface of silica materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Silica-based materials have intensively been studied as adsorbents in solid–liquid separation processes. , Surface-functionalized materials containing cationic groups have thoroughly been used for anion sorption such as arsenate, chromate, perruthenate, perrhenate, or diverse radioelements. , Ammonium- and imidazolium-functionalized silica materials display improved sorption capacities due to the high quantity of functional groups located on the surface of silica materials . Additionally, ionic liquid functionalized silica-based materials appear highly efficient anion exchange materials due to their high sorption capacity, selectivity, reusability, fast kinetics, and efficiency in the large range of pH .…”
Section: Introductionmentioning
confidence: 99%